Localization of liposomal mTHPC formulations within normal epithelium, dysplastic tissue, and carcinoma of oral epithelium in the 4NQO‐carcinogenesis rat model. Issue 10 (30th October 2013) - de Visscher, Sebastiaan A.H.J.; Witjes, Max J.H.; van der Vegt, Bert; de Bruijn, Henriëtte S.; van der Ploeg – van den Heuvel, Angélique; Amelink, Arjen; Sterenborg, Henricus J.C.M.; Roodenburg, Jan L.N.; Robinson, Dominic J.
<x xml:space="preserve">Abstract</x> Background and Objective Foslip and Fospeg are liposomal formulations of the photosensitizer mTHPC (Foscan), which is used for photodynamic therapy (PDT) of malignancies. Literature suggests that liposomal mTHPC formulations have better properties and increased tumor uptake compared to Foscan. To investigate this, we used the 4NQO‐induced carcinogen model to compare the localization of the different mTHPC formulations within normal, precancerous, and cancerous tissue. In contrast to xenograft models, the 4NQO model closely mimics the carcinogenesis of human oral dysplasia. Materials and Methods Fifty‐four rats drank water with the carcinogen 4NQO. When oral examination revealed tumor, the rats received 0.15 mg/kg mTHPC (Foscan, Foslip, or Fospeg). At 2, 4, 8, 24, 48, or 96 hours after injection the rats were sacrificed. Oral tissue was sectioned for HE slides and for fluorescence confocal microscopy. The HE slides were scored on the severity of dysplasia by the epithelial atypia index (EAI). The calibrated fluorescence intensity per formulation or time point was correlated to EAI. Results Fospeg showed higher mTHPC fluorescence in normal and tumor tissue compared to both Foscan and Foslip. Significant differences in fluorescence between tumor and normal tissue were found for all formulations. However, at 4, 8, and 24 hours only Fospeg showed a significant difference. The Pearson's correlation between EAI and mTHPC fluorescence proved weak for all formulations. Conclusion In our induced carcinogenesis model, Fospeg exhibited a tendency for higher fluorescence in normal and tumor tissue compared to Foslip and Foscan. In contrast to Foscan and Foslip, Fospeg showed significantly higher fluorescence in tumor versus normal tissue at earlier time points, suggesting a possible clinical benefit compared to Foscan. Low correlation between grade of dysplasia and mTHPC fluorescence was found. Lasers Surg. Med. 45:668–678, 2013. © 2013 Wiley Periodicals, Inc.